2020
DOI: 10.1111/hsc.13129
|View full text |Cite|
|
Sign up to set email alerts
|

Nurses' and midwives' awareness of intimate partner violence‐related mental healthcare and associated factors in Tanzania

Abstract: Although intimate partner violence (IPV) is a significant public health problem in Tanzania, the country's system to provide IPV‐related mental healthcare is not sufficiently prepared to respond to IPV care needs. This study aimed to assess nurses' and midwives' awareness of IPV‐related mental healthcare and associated factors to encourage care provision. A cross‐sectional, anonymous, self‐administered survey was conducted among nurses and midwives in health facilities in the Mbeya region, from December 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Additionally, some countries in East Africa were mentioned mainly in the context of refugees that had come from that country to other countries in search of humanitarian aid, like refugees from Somalia and South Sudan in refugee camps in Kenya and Uganda ( Amnesty International, 2010 ; Horn, 2010 ; Kawaguchi, 2018 ; Liebling et al, 2020a , 2020b ; Muuo et al, 2020 ; Whelan & Blogg, 2007 ). Our review found that resource constraints and the failure of countries to follow WHO guidance were the most common themes that cut across the research studies on post-SGBV service provision in East Africa, although other issues, such as inconsistent provider training and provider bias, were also significant barriers to adequate service provision ( Ajema et al, 2011 ; Ambikile et al, 2021 ; Amnesty International, 2010 ; Dennis et al, 2019 ; Gatuguta et al, 2018 ; Henttonen et al, 2008 ; Muganyizi et al, 2011 ; Nguyen et al, 2016 ; Odwe et al, 2018 ; Tapesana et al, 2017 ; Whelan & Blogg, 2007 ; Zraly et al, 2011 ).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Additionally, some countries in East Africa were mentioned mainly in the context of refugees that had come from that country to other countries in search of humanitarian aid, like refugees from Somalia and South Sudan in refugee camps in Kenya and Uganda ( Amnesty International, 2010 ; Horn, 2010 ; Kawaguchi, 2018 ; Liebling et al, 2020a , 2020b ; Muuo et al, 2020 ; Whelan & Blogg, 2007 ). Our review found that resource constraints and the failure of countries to follow WHO guidance were the most common themes that cut across the research studies on post-SGBV service provision in East Africa, although other issues, such as inconsistent provider training and provider bias, were also significant barriers to adequate service provision ( Ajema et al, 2011 ; Ambikile et al, 2021 ; Amnesty International, 2010 ; Dennis et al, 2019 ; Gatuguta et al, 2018 ; Henttonen et al, 2008 ; Muganyizi et al, 2011 ; Nguyen et al, 2016 ; Odwe et al, 2018 ; Tapesana et al, 2017 ; Whelan & Blogg, 2007 ; Zraly et al, 2011 ).…”
Section: Discussionmentioning
confidence: 94%
“…(e.g., Manuel et al, 2019). The primary data collection method for understanding medical and legal service provision for IPV survivors was qualitative interviewing, although two studies distributed surveys to medical students, nurses, and midwives (Ambikile et al, 2021;Manuel et al, 2019).…”
Section: Intimate Partner Violencementioning
confidence: 99%
See 3 more Smart Citations